Lending and Cash Required Reserve: Empirical Evidence from Ethiopian Commercial Bank - Yimer, Mitku Malede (European Scientific Journal, ESJ, 2018)
The study was mainly intended to determine the effect of cash required reserve on commercial bank lending in Ethiopia using panel data of eight purposively chosen commercial banks over the period of eleven years (2005 to 2015). The investigation tested the relationship between commercial bank lending and cash required reserve. Eleven years financial data of eight purposively chosen commercial banks were used for analysis purpose. Ordinary least square model was applied to test the impact of predictor variable on commercial bank lending. The result suggests that, there is no significant relationship between commercial bank lending and cash required reserve in Ethiopian commercial. This study suggests that commercial bank have to give less emphasis to cash required reserve because it doesn’t weakens banks credit creation ability and does not leads a bank to be insolvent.